Improving design of chair with flip table (analysis and ergonomics) - Mohd Fahmi, Ismail (2007)
In designing such a product or thing for human use, the 'human factor' is the important element that must put in consideration. One of the things that regularly used by human being to sit is chair. Ergonomic or human factor in the design is a must because the sitting posture has been applied by human whether during learning, eating, in the transport or even in the workstation. The suitability of each chair is depending on the circumstances or situation needed by its user. Research had shown that human product that can be adjustable following to the situation, is a product that consider more about the ergonomics terms. According to the development, the chair design can withstand load of 90kg and the hanger part at the chair can withstand 15kg load, after being analyzed by computer software. The development during the project is to fulfill the learning objective that to produce the frame of chair with adjistable flip table, with using low cost according to the human factor terms. The variety of applications from the project can be use to produce a product based on human factor.